Non‐Newtonian stokes flow with frictional boundary conditions - Saidi, Fouad (Mathematical Modelling and Analysis, 2007)
In this work we deal with the boundary value problem for the non‐Newtonian fluid flow with boundary conditions of friction type, mostly by means of variational inequalities. Among others, theorems concerning existence and uniqueness or non‐uniqueness of weak solutions are presented. First Published Online: 14 Oct 2010